ANALYSIS OF FOCUSED MARKET STRATEGIES FOR IMPROVING CLEAN WATER SUPPLY SERVICES AT PT. AIR MANADO - Nov Stella Exaudia Lario; Jenny Morasa; Claudia WM Korompis (ACCOUNTABILITY, 2023)
This study aims to find out the focused market strategy for implementing procedures and policies for clean water supply activities at PT. Air Manado. The research was conducted using qualitative methods with a case study approach and data collection methods, namely interviews, observation, documentation, and internet research (online research). The research results show that in the supply of clean water, PT. Air Manado implements several procedures and policies that start from processing raw water into clean water, which is then distributed to customers with reference to Minister of Health Decree No. 907/Menkes/SK/VII/. Apart from that, there are also several management policies that have been formed in accordance with the target of PT. Air Manado, whether it's a new connection policy, a tariff policy, or the company's policy in controlling leaks and pipe damage. PT. Air Manado's management strategy, namely the strategy to improve the quality and quantity of clean water, the customer service strategy, the pipeline network expansion strategy, and the performance improvement strategy, will cause the company to lose customers, despite the fact that there are still a lot of complaints and even complaints that occur as a result of non-smooth water distribution. From the research results, it can be concluded that companies should implement a focused market strategy to help overcome problems that are often faced by companies. The strategy implemented is a cost-focus strategy, which is to reduce costs that do not have added value to the clean water produced by the company. The differentiation focus in this case places more emphasis on improving customer service and focusing on improving technology by creating portals that can provide information related to the distribution of clean water and even a 24-hour complaint portal. Keywords: Focused Market Strategy; cost and differentiation.